Graviatoms with de Sitter Interior - Irina Dymnikova; Michael Fil’chenkov (Advances in High Energy Physics)
We present a graviatom with de Sitter interior as a new candidate to atomic dark matter generically related to a vacuum dark energy through its de Sitter vacuum interior. It is a gravitationally bound quantum system consisting of a nucleus represented by a regular primordial black hole (RPBH), its remnant or gravitational vacuum soliton G-lump, and a charged particle. We estimate probability of formation of RPBHs and G-lumps in the early Universe and evaluate energy spectrum and electromagnetic radiation of graviatom which can in principle bear information about a fundamental symmetry scale responsible for de Sitter interior and serve as its observational signatures.